Accuracy of fine-needle aspiration and frozen section for the detection of squamous metastasis in cystic masses of the lateral neck. Issue 9 (November 2022) - Tofanelli, Margherita; Rigo, Stefania; Polesel, Jerry; Zanconati, Fabrizio; Bonazza, Deborah; Marcuzzo, Alberto Vito; Gardenal, Nicoletta; Boscolo-Rizzo, Paolo; Tirelli, Giancarlo
Abstract: Cystic masses of the lateral neck are mostly benign. However, the incidence of metastatic squamous cell carcinoma (SCC) in cervical cystic masses initially diagnosed as benign is quite high in patients older than 40 years. The aim of this study was to compare the diagnostic accuracy of preoperative cytology and intraoperative frozen section (FS) in detecting malignancy in cystic masses of the neck. We reviewed 61 patients who underwent preoperative ultrasound-guided fine-needle aspiration cytology (FNAC) and neck biopsy of a cystic neck mass, and analysed the concordance between FNAC and intraoperative FS with respect to definitive histology. HPV status was also tested. Of 49 eligible cases, the accuracy of preoperative FNAC was 70.5% (weighted kappa 0.53), meaning moderate agreement between cytology and final diagnosis. Intraoperative FS consultations detected 16 cases of SCC metastasis while the remaining 33 cases were negative for SCC, showing perfect agreement with histology. Since FS results were useful in evaluating cystic neck masses, despite a moderate accuracy of cytology, we suggest intraoperative FS analysis for all cystic neck masses. This technique can allow us to switch to therapeutic neck dissection, multiple upper aerodigestive tract biopsies, tongue base mucosectomy, and bilateral tonsillectomy in the same surgical setting.